2019
DOI: 10.3390/toxins11050275
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis: From a Plant That Modulates Feeding Behaviors toward Developing Selective Inhibitors of the Peripheral Endocannabinoid System for the Treatment of Obesity and Metabolic Syndrome

Abstract: In this review, we discuss the role of the endocannabinoid (eCB) system in regulating energy and metabolic homeostasis. Endocannabinoids, via activating the cannabinoid type-1 receptor (CB1R), are commonly known as mediators of the thrifty phenotype hypothesis due to their activity in the central nervous system, which in turn regulates food intake and underlies the development of metabolic syndrome. Indeed, these findings led to the clinical testing of globally acting CB1R blockers for obesity and various meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 154 publications
(158 reference statements)
1
23
0
1
Order By: Relevance
“…Additionally, our observations also highlight the role of these lipids in growth/development and other phenotypes, which can be linked to metabolic status. As summarized, previous studies have already shown connections between nutrient status, metabolism and various components of the ECs in mammals [75][76][77]. It would thus be interesting to see if these newly identified EC-like molecules and FAs might play a crucial role in altering and modulating the metabolic status by interacting with key nutrient sensing and signaling pathways.…”
Section: Discussionmentioning
confidence: 86%
“…Additionally, our observations also highlight the role of these lipids in growth/development and other phenotypes, which can be linked to metabolic status. As summarized, previous studies have already shown connections between nutrient status, metabolism and various components of the ECs in mammals [75][76][77]. It would thus be interesting to see if these newly identified EC-like molecules and FAs might play a crucial role in altering and modulating the metabolic status by interacting with key nutrient sensing and signaling pathways.…”
Section: Discussionmentioning
confidence: 86%
“…As presented earlier, experimental data highlighted the therapeutic potential of CB1R blockade in renal fibrosis and CKD, regardless of the cause (metabolic or not) ( 12 , 13 , 15 18 , 45 ). Therefore, there is a growing interest for the industry to develop CB1R inhibitors with no BBB passage to improve tolerance compared with rimonabant ( 188 ).…”
Section: Cb1r Inhibition: a New Promising Therapeutic Target In Chronic Kidney Diseasesmentioning
confidence: 99%
“…The signaling pathway and synthesis of endocannabinoid(s) are commonly dependent on externally stimulated factors such as metabolic dysregulation, cellular stress, and damage of tissue(s) [ 169 , 171 ]. Although ECS regulation is directed to change in response to obesity, the peripheral organs or the brain region of the body in response to obesity or after a high-fat diet stimulate the ECS [ 146 , 169 , 172 ]. A potential mechanism of the activation of the ECS may consist of an increased level of fatty acids in the diet.…”
Section: Autoimmune Disorders and Cannabinoidsmentioning
confidence: 99%